Correlation of Chemical and Electrochemical Catalysis-Importance of Half Reactions: The Case of Catalytic Oxidation of Ferrous Sulfate by Molecular Oxygen. Issue 5 (23rd March 2018) - Chauhan, Nilam L.; Dameera, Varun; Juvekar, Vinay A.; Mahajani, Sanjay M.; Suresh, Akkihebbal K.; Sarkar, Arindam
Abstract : Catalytic oxidation of ferrous sulfate with molecular oxygen in 0.5 M H2 SO4 has been studied on carbon supported platinum catalyst. Analysis of this catalytic chemical reaction as two distinct electrochemical half reactions proceeding on the catalyst surface is presented. Further, it is proposed that the catalytic chemical reaction can be studied based on mixed potential theory. Pertinent results for the proposal are presented in terms of conversions to ferric ions and the potential acquired by the electrode when immersed in an oxygen saturated solution of ferrous sulfate (mixed potential). The two individual half reactions have been studied separately to obtain key electrochemical parameters through rotating disk electrode experiments. A theoretical approach is also presented that would enable analysis of the catalytic chemical reaction through few electrochemical parameters. The results obtained clearly demonstrate that a greater understanding of various mechanistic aspects of a catalytic chemical reaction can be achieved if it is studied as two or more distinct electrochemical half reactions connected through an electron transfer mechanism.